Rural Load Management using Information Technology - R L Chakrasali; H.N. Nagaraja; B.S. Shavaladi; V.R. Sheelavant (Bulletin of Electrical Engineering and Informatics, 2012)
The mismatch between the generation and demand for electrical power is increasing at an alarming rate. This is mainly due shortage of conventional resources, use of appropriate technology for alternate energy sources and lack of awareness about energy conservation. Power supply to domestic, commercial and industrial consumers is a difficult task to the utilities controlled by the government. In rural India, irrigation pump sets are the major loads. The technical aptitude, attitude and co operation of the consumers helps a lot in energy management. The strategic power supply is affected if the consumers are not complying with the norms. A strategy is framed to provide power to domestic appliances around the clock and agricultural consumers on time division basis. But the local technicians play a corruptive role to violate this which is leading to overloading/failure of the distribution transformers frequently. Here, an attempt is made to devise a method to overcome the problem of agricultural consumers who are getting power on time division basis.  A control unit is installed at each distribution station to automatically monitor and control the power supply to domestic and agricultural consumers as per the pre defined schedule.  This paper explains the use of electronics and information technology in rural areas for better management of the power supply and consumption. The unauthorized connection leading to failure of distribution transformers is also taken care.